Decreased Medical Care During the COVID-19 Pandemic – A Comprehensive Analysis of Radiological Examinations - Fleckenstein, Florian Nima; Maleitzke, Tazio; Böning, Georg; Kahn, Johannes; Büttner, Laura; Gebauer, Bernhard; Aigner, Annette; Hamm, Bernd (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Objectives As a cross-section discipline within the hospital infrastructure, radiological departments might be able to provide important information regarding the impact of the COVID-19 pandemic on healthcare. The goal of this study was to quantify changes in medical care during the first wave of the pandemic using radiological examinations as a comprehensive surrogate marker and to determine potential future workload.Methods A retrospective analysis of all radiological examinations during the first wave of the pandemic was performed. The number of examinations was compared to time-matched control periods. Furthermore, an in-depth analysis of radiological examinations attributed to various medical specialties was conducted and postponed examinations were extrapolated to calculate additional workload in the near future.Results A total of 596,760 examinations were analyzed. Overall case volumes decreased by an average of 41 % during the shutdown compared to the control period. The most affected radiological modalities were sonography (–54 %), X-ray (–47 %) followed by MRI (–42 %). The most affected medical specialty was trauma and orthopedics (–60 % case volume) followed by general surgery (–49 %). Examination numbers increased during the post-shutdown period leading to a predicted additional workload of up to 22 %.Conclusion This study shows a marked decrease in radiological examinations in total and among several core medical specialties, indicating a significant reduction in medical care during the first COVID-19 shutdown.Key Points:Citation Format
Keywords: healthcare; shutdown; SARS-CoV-2; workload; economics lockdown